Private Yokoi's war and life on Guam, 1944-1972 : the story of the Japanese Imperial Army's longest WWII survivor in the field and later life - Omi, Hatashin (Global Oriental, 2009)
"This book is about the reality of such a man (and the ingenuity he applied to ensure his survival), which is very different from the stereotype. The first part is the English translation of his own autobiography, which was narrated to his wife who wrote everything down. The second part is a biography of Yokoi after his return to Japan, including his marriage, upper house elections in 1974, his pottery and his views on modern life. He died in 1997. Although Intelligence Officer Onoda's story of survival on Lubang caught the headlines in the same year (1974) that Yokoi published his story, it is interesting to note that Yokoi, a mere Private, did not attract the same amount of interest in Japan, partly because of stories of 'cowardice' and partly because he was simply a nobody in the Imperial Japanese Army and therefore an embarrassment. This book, therefore, sheds a different light on the reality of the war in the Pacific while addressing some key issues concerning the nature of Japanese culture in modern times"--Publisher's website